Conformity analysis to demonstrate reproducibility of target volumes for Margin-Intense Stereotactic Radiotherapy for borderline-resectable pancreatic cancer. Issue 1 (October 2016) - Holyoake, Daniel L.P.; Robinson, Maxwell; Grose, Derek; McIntosh, David; Sebag-Montefiore, David; Radhakrishna, Ganesh; Patel, Neel; Partridge, Mike; Mukherjee, Somnath; Hawkins, Maria A.
Abstract: Background and purpose: Margin-directed neoadjuvant radiotherapy for borderline-resectable pancreatic cancer (BRPC) aims to facilitate clear surgical margins. A systematic method was developed for definition of a boost target volume prior to a formal phase-I study. Material and methods: Reference structures were defined by two oncologists and one radiologist, target structures were submitted by eight oncologist investigators and compared using conformity indices. Resultant risk of duodenal bleed (NTCP) was modelled. Results: For GTV, reference volume was 2.1 cm 3 and investigator mean was 6.03 cm 3 (95% CI 3.92–8.13 cm 3 ), for boost volume 1.1 cm 3 and 1.25 cm 3 (1.02–1.48 cm 3 ). Mean Dice conformity coefficient for GTV was 0.47 (0.38–0.56), and for boost volume was significantly higher at 0.61 (0.52–0.70, p = 0.01). Discordance index (DI) for GTV was 0.65 (0.56–0.75) and for boost volume was significantly lower at 0.39 (0.28–0.49, p = 0.001). NTCP using reference contours was 2.95%, with mean for investigator contour plans 3.93% (3.63–4.22%). Correlations were seen between NTCP and GTV volume ( p = 0.02) and NTCP and DI (correlation coefficient 0.83 (0.29–0.97), p = 0.01). Conclusions: Better conformity with reference was shown for boost volume compared with GTV. Investigator GTV volumes were larger than reference, had higher DI scores and modelled toxicity risk. A consistent method of target structure definition for margin-directed pancreatic radiotherapy is demonstrated.